Effect of educational video on newborn care for the knowledge of pregnant and postpartum women and their families - Leilane Barbosa de Sousa; Hévila Ferreira Gomes Medeiros Braga; Aynoan de Sousa Amaro Alencastro; Maria Jocelane Nascimento da Silva; Brena Shellem Bessa de Oliveira; Lydia Vieira Freitas dos Santos; Emanuella Silva Joventino Melo (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to evaluate the effect of educational video on newborn care to increase the knowledge of pregnant, postpartum, and family members. Methods: a quasi-experimental study, with pre-intervention and post-intervention evaluation with a single group. Fifty-eight pregnant, postpartum, and family members treated in basic health units and a hospital in Ceará, Brazil, participated. The study used the McNemar and binomial tests for the analysis. Results: after the intervention, there was an increase in the frequency of hits, from 70.82% to 92.97%. Most of the questions presented a significant increase of hits (p < 0.05) with an emphasis on sleeping position, drying of clothes, free demand for breastfeeding, and things to avoid (such as accessories in the sleeping place and talc in diaper change). Conclusions: the educational video was effective to participants in acquiring knowledge on the care of newborns and can assist in health education activities carried out by nurses.